Role of computed tomography in non-traumatic acute abdomen in adults - Rachna Chaurasia; Pratyush Kumar (Asian Journal of Medical Sciences, 2022)
Background: The objective of this study was to study, assess, and diagnose causes of acute abdomen accurately, to determine the accuracy of multidetector computed tomography (CT) for confirmation of negative, diagnosed, or equivocal ultrasonography (USG) cases, and to establish role of CT as the primary imaging modality. Aims and Objective: To study, assess and diagnose causes of acute abdomen accurately, To determine the accuracy of MDCT for confirmation of Negative, diagnosed or equivocal USG cases & To establish role of CT as the primary imaging modality. Materials and Methods: One hundred and twenty random patients were included in this prospective study. USG and CT were done in all patients. Axial, coronal, and sagittal reformatted images were studied. Intravenous and oral contrast were also used depending on the clinical condition. All these patients were followed up diagnosis obtained before and after CT were compared with intraoperative findings or final clinical diagnosis at discharge. Results: Among 120 patients, confirmative CT diagnosis was made in 111 cases and was discordant in seven cases, while two cases could not be followed up. Forty-five cases underwent surgical management and rest of them were managed medically. Conclusion: CT abdomen done in patients presenting with non-traumatic acute abdominal pain which helps to make accurate diagnosis and planning the appropriate treatment.